Can Joint Training Increase Union Knowledge and Power? - Olson, Corliss (Just Labour: A Canadian Journal of Work and Society, 2005)
Globalization has been accompanied by a decline in unionization; however, while globalization presents extremely serious challenges to unions, globalization does not necessarily result in weakened unions. It is important for unions to identify and utilize ways to increase and leverage union power that are responsive to the pressures of globalization. Companies frequently introduce training during restructuring efforts aimed at remaining competitive in a global environment. This paper describes a joint union-management training program which offers an example of a pro-active union approach to joint training initiatives. The training took place in early 2004 in a typical paper mill in central Wisconsin. While the training was designed and undertaken in response to various competitive pressures, the content of the training was primarily determined by employee focus groups. The training design is examined against criteria for successful union involvement in joint ventures. The paper argues that, while joint ventures typically address management's production concerns at the expense of labor, a pro-active union can work to ensure that benefits also accrue to the union. Recent literature on union power in a globalized economy suggests that this training model could be used in other industries to enhance union knowledge and power.